South-South cooperation: a case study of contemporary Sudanese-Malaysian relations - Eissa, Garoot Suleiman; Abdel Salam, El Fatih Abdullahi; Omar, Muhamad Fuzi (IIUM Press, International Islamic University Malaysia, 2019)
South-South cooperation is an approach to international economic and political relations among developing countries to enhance development prospects; it has been increasing in significance. Such a strategy was adopted bilaterally at the outset between Malaysia and Sudan but eventually evolved to include a broader network of Asian and African Countries. This paper is focused on Malaysia-Sudan relations as a case study. It adopts a qualitative approach comprising reliance on primary and secondary sources of data to study the relations of exchange between the two countries. Findings lend support to claims of potential rewards in South-South Cooperation. Through it Sudan managed to exploit its idle oil reserves and achieve high rates of economic growth. Similarly, Malaysia achieved very good results in areas of trade and investment and managed to open up business opportunities in other African countries. Sudan was also able to build productive cooperation with a number of Asian countries. All countries involved benefited from the cooperation.